PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW DALAM PEMBELAJARAN IPS TERHADAP SIKAP KEPEDULIAN SOSIAL PESERTA DIDIK KELAS VII SMP - Umi Thohiroh; Yadi Suryadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the decline in students' social awareness, characterized by low levels of empathy, cooperation, and responsibility in Social Studies learning. This study aims to analyze the differences and examine the effect of the Jigsaw Cooperative Learning model on the social awareness of seventh-grade students at SMPN 7 Semarang. This study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The research sample consisted of 60 students, with Class VII B as the experimental group and Class VII F as the control group. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability (Cronbach’s Alpha = 0.914). Data analysis included normality and homogeneity tests, followed by hypothesis testing using an independent samples t-test. The results showed that the mean posttest score of the experimental group (103.40) was higher than that of the control group (84.20). The hypothesis testing revealed a Sig. (2-tailed) value of 0.000 < 0.05 and a t-value of 16.892 > 2.002, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the Jigsaw Cooperative Learning model has a significant effect on improving students' social awareness in Social Studies learning. ABSTRAK Penelitian ini dilatarbelakangi oleh menurunnya sikap kepedulian sosial peserta didik yang ditandai dengan rendahnya empati, kerja sama, dan tanggung jawab dalam pembelajaran IPS. Penelitian ini bertujuan untuk menganalisis perbedaan serta menguji pengaruh model Cooperative Learning tipe Jigsaw terhadap sikap kepedulian sosial peserta didik kelas VII SMPN 7 Semarang. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi experimental jenis non-equivalent control group design. Sampel penelitian berjumlah 60 peserta didik yang terdiri atas kelas VII B sebagai kelas eksperimen dan VII F sebagai kelas kontrol. Teknik pengumpulan data menggunakan angket skala Likert yang telah diuji validitas dan reliabilitasnya (Cronbach’s Alpha = 0,914). Analisis data meliputi uji normalitas, homogenitas, dan uji hipotesis menggunakan independent sample t-test. Hasil penelitian menunjukkan rata-rata posttest kelas eksperimen (103,4) lebih tinggi dibandingkan kelas kontrol (84,20). Hasil uji hipotesis menunjukkan nilai Sig. (2-tailed) sebesar 0,000 < 0,05 dan t hitung 16,892 > t tabel 2,002, sehingga H₀ ditolak dan Hₐ diterima. Dengan demikian, model Cooperative Learning tipe Jigsaw berpengaruh signifikan terhadap peningkatan sikap kepedulian sosial peserta didik pada pembelajaran IPS.